Novel interactions of dissipative Kerr solitons in nonlinear cavity networks - Munns, J; Walmsley, I; Wen, Y (Institute of Electrical and Electronics Engineers, 2017)
Kerr micro-resonator frequency combs exhibit a variety of nonlinear phenomena, most prominently the formation of dissipative Kerr solitons (DKSs). These solitons are critical for applications in frequency metrology, precision time-keeping and ultrashort pulse generation. Thus far all studies of DKSs have been limited to single cavities or two uncoupled cavities, though coupled dual microring resonators with the potential for generating DKS in both ring cavities have been demonstrated. Inspired by multi-soliton interactions and synchronization of coupled modelocked lasers, we numerically investigate the dynamics of DKSs in a network of coupled cavities. Given its scalable and phase sensitive nature such a system is expected to exhibit even richer nonlinear phenomena with the potential to enable new technologies.